Effect of Curing Process on Composition of Indonesian Bay Leaf (Eugenia polyantha Wight.): Components’ Profile and Preference of Flavor Extracted by Simultaneous Distillation-Extraction Method - Wartini, Ni Made; Harijono, Harijono; Susanto, Tri; Retnowati, Rurini; Yunianta, Yunianta (Fakultas Teknologi Pertanian Universitas Brawijaya, 2007)
Bay leaves are widely used as flavouring in Indonesian cuisine, either in the form of fresh ones or after naturally dried, known as curing process. The research was conducted to determine the profile of components of the Indonesian cured bay leaves and to determine the preference of its flavour extracted by simultaneous distillation-extraction method. A randomized block design experiment was performed examining three levels of curing time, namely 0, 2 and 4 days. The effects of curing on the change of weight, moisture content, colour, and components profile of the bay leaves were evaluated. The flavour components from all samples were isolated by simultaneous distillation-extraction method. The hedonic scale scoring was used to evaluate the preference of the flavour of the extract. It was found that the curing process substantially reduced the weight and moisture content, as well as the colour of the leaves. A total of 27, 33 and 23 compounds were resulted from flavour extract of 0, 2, 4 days cured bay leaves, respectively. The flavour extracts from 0 and 2 days cured bay leaves showed no difference in the preference test. Key words: curing, flavour, bay leaf.